Basic Statistics Relating to the Indian Economy 1950-51 to 1960-61 - Planning Commission (Planning Commission, 1961)
The document “Statistical Overview of the Indian Economy (1950–1961)” provides a comprehensive analysis of India’s economic performance during the first two Five-Year Plans. National income and per capita income grew steadily, with agriculture and industrial production showing significant expansion. Electricity generation and installed capacity surged, particularly in steam and hydro power, supporting increased industrial consumption. Trade patterns reflected rising exports and variable imports, while wholesale and consumer prices indicated moderate inflation. Public finance analysis highlighted growth in central and state government debt, money supply, and banking sector consolidation, alongside increasing insurance sector activity. Education and workforce indicators demonstrated rising enrolment, teacher numbers, and employment in railways and commercial sectors. Population trends showed urbanization around industrial hubs. Overall, the statistics depict a transformative decade with notable progress in infrastructure, energy, and economic development, while also revealing challenges in fiscal management, urban planning, and equitable living standards, providing critical insights for policymakers and researchers.
Statistics & Surveys Division Planning Commission New Delhi
Statistics & Surveys Division Planning Commission New Delhi
Keywords: Indian Economy; Statistical Overview; Five Year Plans; National Income; Per Capita Income; Agricultural Production; Industrial Production; Electricity Generation; Hydro Power; Steam Power; Trade Patterns; Imports; Exports; Price Indices; Banking Sector